The effects of job demands on nurses' burnout and presenteeism through sleep quality and relaxation. Issue 3 (9th December 2019) - Gillet, Nicolas; Huyghebaert-Zouaghi, Tiphaine; Réveillère, Christian; Colombat, Philippe; Fouquereau, Evelyne
Abstract: Aims and objectives: The main aim of this study was to investigate the indirect effects of emotional dissonance and workload on presenteeism and emotional exhaustion through sleep quality and relaxation. Background: Numerous investigations have found that job demands are related to employees' health and behaviours, but additional studies are needed among nurse samples. Specifically, little is known about the relationships between nurses' emotional dissonance and workload on one hand, and presenteeism and emotional exhaustion on the other hand. Moreover, research is needed to further explore the psychological mechanisms underlying these relationships. Design: We used a cross‐sectional design. Our study was carried out between October 2015–February 2016. Precisely, we asked nurses from various French healthcare centres to fill out a questionnaire survey. We ensured to meticulously follow the STROBE guidelines for cross‐sectional research in designing and reporting this study. Method: An empirical study with a sample of 378 nurses was conducted. Results: In line with our hypotheses, our findings revealed that emotional dissonance and workload were negatively linked to sleep quality and relaxation, which were, in turn, related to lower levels of presenteeism and emotional exhaustion. Workload and emotional dissonance were also directly and positively related to emotional exhaustion, while emotional dissonance was associated with higher levels of presenteeism. Finally, the indirect effects of emotional dissonance and workload on emotional exhaustion through sleep quality as well as the indirect effects of emotional dissonance on emotional exhaustion through relaxation were significant and positive. Conclusions: Overall, our results provide insight into the effects of emotional dissonance and workload on presenteeism and emotional exhaustion through recovery processes. Relevance to clinical practice: The present findings have some practical implications for reducing nurses' emotional exhaustion and presenteeism. Specifically, managers and organisations should try to design and craft jobs to decrease the presence of negative work characteristics (i.e., workload and emotional dissonance). Our results also suggest that recovery processes may be important factors to focus on.